1998
DOI: 10.1016/s0022-2275(20)33881-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of deuterium incorporation against sterol balance for measurement of human cholesterol biosynthesis

Abstract: To examine the validity of the deuterium (D) incorporation technique for measurement of human cholesterol synthesis rates, D uptake from D 2 O into cholesterol was compared to sterol balance in 13 subjects each under three controlled diet settings. Subjects (age 62 ؎ 3.6 yr, body weight 74 ؎ 4.0 kg, BMI 27 ؎ 1.4) consumed weight maintenance diets enriched in either corn oil, beef tallow, or stick corn oil margarine over a 5-week period. During the final week of the study period, subjects were given 1.2 g/ D 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…As circulating cholesterol levels reflect changes in synthesis and clearance, it can be speculated that the enhanced biosynthesis seen with SO, SQM, and TM feeding was compensated by an even greater rate of clearance, which could, in part, explain the lower lipid levels seen after consumption of these diets. This hypothesis is consistent with the findings of increased net fecal neutral and acidic sterol excretion seen with corn oil feeding compared to stick margarine or beef tallow (28). Conversely, despite marked suppression of synthesis, the higher plasma TC and LDL-C levels seen on the SM, BT, and BL diets suggest some impairment in the catabolic pathway of cholesterol.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As circulating cholesterol levels reflect changes in synthesis and clearance, it can be speculated that the enhanced biosynthesis seen with SO, SQM, and TM feeding was compensated by an even greater rate of clearance, which could, in part, explain the lower lipid levels seen after consumption of these diets. This hypothesis is consistent with the findings of increased net fecal neutral and acidic sterol excretion seen with corn oil feeding compared to stick margarine or beef tallow (28). Conversely, despite marked suppression of synthesis, the higher plasma TC and LDL-C levels seen on the SM, BT, and BL diets suggest some impairment in the catabolic pathway of cholesterol.…”
Section: Discussionsupporting
confidence: 85%
“…While this may be true, the initial, short term deuterium oxide incorporation rate is linear (13,22), unaffected by flux rates of other unlabeled substances into the system and thus can be taken to represent a direct measure of synthesis independent of total whole body production rate. In addition, the DI method has been compared and validated against the classic sterol balance technique (28). More recently, Di Buono et al (37) measured fractional and absolute synthesis rates of cholesterol simultaneously by the DI and mass isotopomer distribution analysis (MIDA) methods.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol biosynthesis was determined as the rate of incorporation of deuterium from body water into RBC membrane free cholesterol over the period between 72 and 96 h at the end of each treatment as described (19). Fractional synthesis rate (FSR) represents that fraction of the cholesterol pool that is synthesized in 24 h and is calculated as per the equation (20,21):…”
Section: Determination Of Cholesterol Biosynthesis and Turnovermentioning
confidence: 99%
“…Reviews have assessed the impact of precursor pool nonhomogeneity in the broader context of MID analysis of intermediary metabolism (7,32). Puchowicz et al (33) showed in dogs infused with [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]acetate via transhepatic catheters that the enrichment of acetate decreases markedly across the liver due to hepatic production of unlabeled acetate from acetyl-CoA. This may support the existence of multiple acetyl-CoA pools; however, precisely which of these pools would serve as the precursor of cholesterol is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Both deuterium incorporation (5,10,13,14,30,35) and MIDA (7,12,15,16,(36)(37)(38) have been applied to study cholesterol synthesis under various metabolic conditions (Table 4). DI has been evaluated against the cholesterol balance technique, which is considered the standard of choice for measurement of synthesis over the long term (8), showing a strong correlation (r ϭ 0.745, P Ͻ 0.0001) between synthesis measured by sterol balance (17.7 Ϯ 1.7 mg kg Ϫ1 day Ϫ1 ) and DI (15.9 Ϯ 1.2 mg kg Ϫ1 day Ϫ1 ). DI is also highly correlated with plasma cholesterol precursors (9, 10) as indices of short-term synthesis.…”
Section: Discussionmentioning
confidence: 99%